Effect of omega‐3 fatty acids supplementation on indirect blood markers of exercise‐induced muscle damage: Systematic review and meta‐analysis of randomized controlled trials - Gao Xin (Wiley, 2021)
Abstract Background Omega 3 fatty acids supplementation may have an attenuative effect on exercise‐induced muscle damage (EIMD) through the cell membrane stabilization. The purpose of the present meta‐analysis was to evaluate the effects of omega 3 fatty acids supplementation, on indirect blood markers of muscle damage following EIMD in trained and untrained individuals. Methods Scopus, Medline, and Google scholar systematically searched up to January 2021. The Cochrane Collaboration tool was used for the quality of studies. Random‐effects model, weighted mean difference (WMD), and 95% confidence interval (CI) were applied for the overall effect estimating. The heterogeneity between studies was evaluated applying the chi‐squared and I2 statistic. Results The outcomes showed a significant effect of omega 3 supplementation on reducing creatine kinase (CK), lactate dehydrogenase (LDH), and myoglobin (Mb) concentrations. In addition, a subgroup analysis indicated a significant reduction in CK, LDH, and Mb concentrations, based on follow‐ups after exercise, studies duration, time of supplementation, and training status. Conclusion The current meta‐analysis indicated an efficacy of omega 3 in reducing CK, LDH, and Mb serum concentration among healthy individuals, overall and in subgroups analysis. Thus, omega 3 should be considered as a priority EIMD recovery agent in interventions.